2021
DOI: 10.1029/2020jf005709
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Preonzo Rock Slope Instability Using Resonance Mode Analysis

Abstract: We monitored an unstable rock slope using frequency domain decomposition modal analysis • We tracked the resonance frequency, mode shapes, and damping ratio of the fundamental and first higher mode over a period of four years • Our study shows seasonal variations of all dynamic parameters and a weak linear relationship between frequency and damping ratio Accepted ArticleThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, paginatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
(90 reference statements)
2
16
0
Order By: Relevance
“…No corresponding peaks appear on any of the reference stations, indicating that these are modal frequencies of the unstable slab. FDD analysis of the geophone array (e.g., Häusler et al., 2019, 2021) confirmed that the spectral peaks observed from PSD analysis should be interpreted as normal‐mode eigenfrequencies (Figure S2 in Supporting Information S1). In a few instances, spectral peaks appear on several, but not all, array stations, which may be related to local site effects (e.g., resonance of the cliff edge).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…No corresponding peaks appear on any of the reference stations, indicating that these are modal frequencies of the unstable slab. FDD analysis of the geophone array (e.g., Häusler et al., 2019, 2021) confirmed that the spectral peaks observed from PSD analysis should be interpreted as normal‐mode eigenfrequencies (Figure S2 in Supporting Information S1). In a few instances, spectral peaks appear on several, but not all, array stations, which may be related to local site effects (e.g., resonance of the cliff edge).…”
Section: Resultsmentioning
confidence: 88%
“…The short acquisition time, non-invasive nature and repeatability of ambient vibration cross-correlation from dense array data, as demonstrated here for the Courthouse Mesa rock slope instability, offer promise to the applicability of structural characterization using this technique at other landslide sites. With adequate access, this experiment could also be repeated on a seasonal or annual basis or after strong external forcing (e.g., earthquakes or the cumulative effects of thermal loading) to identify recoverable environmentally driven changes and potentially detect permanent structural damage (Colombero et al, 2018(Colombero et al, , 2021Häusler et al, 2021). For example, differences in mode shapes observed during a repeat summer measurement at Courthouse Mesa could provide insight on structural changes occurring at depth when the crack reaches its minimum summertime aperture at the surface (Figure 2a).…”
Section: Implications For Structural Characterization Of Rock Slope I...mentioning
confidence: 99%
“…High amplification in distinct frequency bands might indicate normal-mode behaviour, that is a standing wave phenomenon caused by waves trapped between fractures. To investigate this phenomenon, we applied the frequency domain decomposition (FDD) technique for normal-mode analysis, which is a standard technique in structural engineering but has found broad application on geological features such as sedimentary valleys and rock slope instabilities (Brincker et al 2001;Michel et al 2010;Bottelin et al 2013;Poggi et al 2015;Häusler et al 2021;Mercerat et al 2021). The crosspower spectral density matrix of all input traces of ambient vibration data is computed and decomposed in its singular values and singular vectors.…”
Section: Ambient Vibration Array Data Acquisition and Processingmentioning
confidence: 99%
“…This is especially beneficial before or in the early stage of continuous landslide monitoring to plan the monitoring setup and to bypass the early monitoring period, when measured displacements are too small to reliably determine displacement vectors. However, studies on other rock instabilities showed that polarization is not solely governed by fracture geometry, but possibly also by other parameters such as material stiffness distribution (Häusler et al 2021).…”
Section: O N C L U S I O N S a N D I M P L I C At I O N S F O R L A N...mentioning
confidence: 99%
See 1 more Smart Citation